An application of constacyclic codes to entanglement-assisted quantum MDS codes - Sari, Mustafa; Kolotoglu, Emre (SPRINGER HEIDELBERG, 2019)
The constructions of entanglement-assisted quantum codes have been studied intensively by researchers. Nevertheless, it is hard to determine the number of shared pairs required for constructing entanglement-assisted quantum codes from linear codes. In this paper, by making use of the notion of decomposition for defining sets of constacyclic codes, we construct several new families of entanglement-assisted quantum MDS codes from constacyclic codes, some of which are of minimum distances greater than q + 1. Moreover, we tabulate their parameters to illustrate what we find in this paper.
Keywords: Entanglement-assisted quantum codes; Constacyclic codes; Defining sets; DISTANCE; Mathematics